2002
DOI: 10.1046/j.1439-037x.2002.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties of Eroded Soil Material

Abstract: In a 5-year stationary investigation at an experimental station in central Croatia, total amounts of erosional drift were measured on a Stagnic Luvisol on which six tillage methods were used. The chemical properties of the tilled soil and the erosional drift were recorded for each trial method in the same plots. A generally higher soil reaction value, higher organic matter content and larger amounts of available phosphorus and potassium were found in the majority of erosional drifts compared to plot soil. On b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
(35 reference statements)
5
7
0
Order By: Relevance
“…These results are consistent with the results of other researchers: Burwel et al (1977), McIsaac et al (1991), Fleige and Horn (2000), Kisic et al (2002), Ali et al (2006), Malam Issa et al (2006) and Warrington et al (2009) reported higher content of OM, plant available nutrients and other chemicals in soil sediments. Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with the results of other researchers: Burwel et al (1977), McIsaac et al (1991), Fleige and Horn (2000), Kisic et al (2002), Ali et al (2006), Malam Issa et al (2006) and Warrington et al (2009) reported higher content of OM, plant available nutrients and other chemicals in soil sediments. Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage.…”
Section: Resultssupporting
confidence: 93%
“…This indicates an increase in the ER OC with increasing soil loss rate, which is rather unusual and may be a result of the difference in tillage technique; however, the results of Cogle et al (2002) indicated that the kind of tillage technique affected the sediment yields but did not directly infl uence the ER OC . This was also observed by and Kisic et al (2002) for enrichment of clay and OC, respectively. On the other hand, Fullen (1991) and Fullen et al (1996) found lower OC, clay, and silt concentrations in eroded material compared with the loamy sand topsoil and attributed it to eluviation of clay and organic matter into the topsoil during runoff events.…”
supporting
confidence: 71%
“…Several researchers have indicated that conservation tillage practices reduce losses in soil and organic carbon (SOC) (Mostaghimi et al. , 1988; Kisic et al. , 2002; Puustinen et al.…”
Section: Introductionmentioning
confidence: 99%